PEMBERDAYAAN UMKM PEREMPUAN KOTA DENPASAR DIBIDANG E-COMMERCE - Linawati, Linawati; Wirastutia, N.M.A.E.D.; Widyantara, I.M.O.; Wiharta, D.M.; Mertasana, P.A. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
Micro, Small, Medium Enterprise (MSME) in Indonesia, especially MSME business women in Denpasar – Bali needs innovation using information communicaton technology to expand their business. Then the enterprise can be transformed to be e-commerce. Thus, e-commerce workshop has been designet and implemented for MSME business women in Denpasar City in collaboration with Department of Women and Children empowerment, Denpasar City. From the workshop evaluation results, most of participants were satisfied and their understanding with e-commerce was increased. As a result, the workshop increases their capacity building as a MSME business woman in term of e-commerce. This is shown by their statements that more than 70% of total participant approved the workshop was very effective, and they eager to implement it in their business.